A hybrid technique to secure fingerprint templates using Delaunay neighbour structures. (2016) - Sandhya, Mulagala; Prasad, Munaga V.N.K.
The rampant increase in the use of biometric authentication systems in a variety of applications made template protection for biometrics an important issue to be considered in the past decade. The leakage of biometric information causes privacy threats. Hence, biometric templates should be protected. In this paper, we propose a hybrid method for fingerprint template protection by combining cancellable biometrics and bio-cryptosystems. First, we construct Delaunay neighbour structure (DNS) for all minutia points in the fingerprint image. Second, we transform the DNS of each minutia point based on the distance and orientation difference between the minutia points in the DNS. Third, these transformed features are encrypted by using Bose, Chaudhuri, and Hocquenghem (BCH) error correction code in fuzzy commitment scheme. Hence, a secure template is obtained. An EER of 1.15%, 1.49%, 5.81%, 10.76%, 11.54% and 15.21% is obtained for the proposed method on FVC 2002 DB1, DB2, DB3, FVC 2004 DB1, DB2, and DB3, respectively. Experimental results and analysis prove the efficacy of the proposed method.